2010
DOI: 10.1016/j.pec.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of diagnosis and treatment among early stage prostate cancer survivors

Abstract: Objective-Increased long-term survival rates have led to a greater focus on the health-related quality of life (HRQL) of prostate cancer survivors. This study assessed the motivations of prostate cancer survivors for disclosing their diagnosis and treatment to close others, and their perceptions of their own and others' responses to the disclosure. Methods-Prostate cancer survivors (N = 35) who were 24-36 months post-treatment for localized disease completed a semi-structured telephone interview. Open-ended qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…In the context of dating, disclosure also served as a type of test of the potential partner, whereby his reactions to each progressive disclosure would dictate the further development of the new relationship. Consistent with other disclosure literature [e.g., , women remained hypervigilant to men's reactions and also used the men's receptivity to infer their character and their desirability and safety as long‐term mates.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the context of dating, disclosure also served as a type of test of the potential partner, whereby his reactions to each progressive disclosure would dictate the further development of the new relationship. Consistent with other disclosure literature [e.g., , women remained hypervigilant to men's reactions and also used the men's receptivity to infer their character and their desirability and safety as long‐term mates.…”
Section: Discussionsupporting
confidence: 73%
“…Despite the potential negative reactions that disclosure might entail, there was no doubt in the women's minds that it had to occur. Although most of the current research on disclosure pertains to the process of disclosing a cancer diagnosis to an existing partner or family member [e.g., ], there were some commonalities with the present investigation, such as the motivations behind disclosure, the use of ‘strategies’, and the potential benefits gained as a result. For example, the women in the current study reported various motivations for disclosure, the foremost of which was a sense of obligation to ‘warn’ their prospective partner about their history.…”
Section: Discussionmentioning
confidence: 93%
“…This was consistent with and extended the previous studies on disclosure of a prostate cancer diagnosis to Latinos and articulated the process of prostate cancer communication (Gray et al, 2000; Hilton et al, 2009; Jackson et al, 2010; Papadopoulos & Lees, 2004). …”
Section: Discussionsupporting
confidence: 90%
“…Gray, Fitch, Phillips, Labrecque, and Fergus (2000) found that men were very cautious about disclosing their prostate cancer diagnosis because the idea of needing support and the need to control their anxiety about their diagnosis were linked to discomfort. In the other study, investigators found that men who told members of their social network about their diagnosis received positive support and felt they had done the right thing (Jackson et al, 2010). However, the men in both studies were predominantly Caucasian; minorities were underrepresented in all of the studies reviewed.…”
mentioning
confidence: 99%
“…Disruptions, challenges, and tensions have not been explored for men facing a potential prostate cancer diagnosis as communication with patients in the extant literature tends to be associated with a new diagnosis Greene et al, 2012;Jackson et al, 2010) and later in the medical journey (Gray et al, 2000). However, with few exceptions, (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%